EVALUASI PERAN RUANG TERBUKA HIJAU DALAM MITIGASI EMISI KARBON DIOKSIDA TRANSPORTASI DI SIDOARJO - Nursinta Abadiyah; Okik Hendriyanto Cahyonugroho (LPPM Universitas Abdurrab, 2026)
Urban Green Infrastructure serves a critical function in spatial planning and emission mitigation in cities. This study aims to evaluate UGI located in the city center and the suburban area of Sidoarjo. The research was conducted using traffic counting along the roads adjacent to both parks and tree inventory, including species identification, diameter at breast height (DBH), crown width, tree height, and tree condition. Data analysis employed the IPCC Tier 2 approach, i-Tree Eco, and NDVI processed with ArcGIS. The results indicate that carbon dioxide emissions from motor vehicles were higher at Apkasi Park, located in the suburban area, compared to Abhirama Park, located in the city center. Conversely, CO₂ sequestration capacity showed the opposite trend: Apkasi Park contained 70 trees with a sequestration capacity of 0.39 kg/hour, while Abhirama Park had 159 trees with a sequestration capacity of 0.90 kg/hour. This demonstrates a relatively small percentage of sequestration compared to the emissions produced. NDVI analysis further revealed that Apkasi Park still has sufficient space for additional tree planting, whereas Abhirama Park has already reached a relatively high vegetation density.